Validation of the BetaStar® Advanced for Tetracyclines Test Kit for the Screening of Bulk Tank and Tanker Truck Milks for the Presence of Tetracycline Drug Residues. (23rd November 2019) - Ankrapp, David; Schaus, Benjamin; Clements, Lauren; Klein, Frank; Rice, Jennifer; Rejman, John J; Boison, Joe; Kijak, Philip; Shelver, Weilin
Abstract: A validation study was conducted for an immunochromatographic method (BetaStar ® Advanced for Tetracyclines) for detection of tetracycline antibiotic residues in raw, commingled bovine milk. The assay was demonstrated to detect tetracycline, chlortetracycline, and oxytetracycline at levels below the FDA tolerance levels but above the maximum sensitivity thresholds established by the National Conference on Interstate Milk Shipments. Results of internal and independent laboratory dose-response studies employing spiked samples were in agreement. All three drugs at the approximate 90/95% sensitivity levels were detected in milk collected from cows that had been treated with the specific drug. Selectivity of the assay was 100%, as no false-positive results were obtained in testing 881 control milk samples. Testing the estimated 90/95 sensitivity level for tetracycline (213 ppb), chlortetracycline (272 ppb), and oxytetracycline (180 ppb) and at 1000 ppb for each antibiotic resulted in 100% positive tests for each tetracycline. Results of ruggedness experiments established the operating parameter tolerances for the test. Results of cross-reactivity testing established that the assay detects certain other tetracycline drugs but does not cross-react with any of 32 drugs belonging to seven different drug classes. Abnormally high bacterial or somatic cell counts (SCC) in raw milk produced no assay interference.